Melacak Akar dan Perkembangan Konservatisme Islam dalam Dinamika Perpolitikan Indonesia - Tasnur, Irvan; Zulkarnain, Zulkarnain (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2019)
Conservatism as an ideology has regained attention in the life of the Indonesian people in recent years, this is due to the existence of a series of several major events so that the issue of ideology re-emerges before the public. Along with the rise of ideological issues, the involvement of media framing has led to the formation of negative stigma towards ideology, especially those based on Islamic teachings. This study aims to explore and analyze the process of birth and the development of Islamic conservatism in Indonesia using a historical approach. The results of the analysis that the term conservatism will always be related to traditionality, but the different traditional meanings in each country will cause different forms of conservatism. The meaning of traditionality in Indonesian society is more identical to Islamic groups which, if explored further, is caused by the existence of propaganda to create a sense of inferiority complex that is carried out by the Dutch due to fears of resistance led by Islamic groups. The Islamic struggle to re-establish Islamic teachings in the midst of national life continues after Indonesia's independence up to now with various forms, one of which is the political party that makes Islam the sine qua non and raison d'?tre of the party, these Islamic parties continue dwelling on the dynamics of Indonesian history to date which are detailed in this article.